The Effects of Project Portfolio Management on Competitive Advantage through Dynamic Capability (Global Journals of Research in Engineering, 2019)
A business firm needs to respond and adapt to the changing business environment in order to achieve and sustain the competitive advantages in the fast changing and very competitive market of today. Business strategy is an important discipline that provides the guidelines on how to deal with the changing business environment and to develop competitive advantages.The theory development and discussion in the business strategy discipline shows a trend change from the external environment analysis theory by M.E. Porter in the 1980s, to Resource Based View(RBV)in the 1990s, and to the dynamic capability theory in the late 1990s. Another effort by business firms to cope with the changing business environment may be the development and application of project management theories such as project portfolio management.
Keywords: project portfolio management; project management; dynamic capability; competitive advantage